Costs of illness and quality of life in patients with systemic lupus erythematosus in South Korea. (August 2014) - Cho, JH; Chang, SH; Shin, NH; Choi, BY; Oh, HJ; Yoon, MJ; Lee, EY; Lee, EB; Lee, TJ; Song, YW
Objective: To assess the costs of illness, health-related quality of life (HRQOL) and their associated factors in patients with systemic lupus erythematosus (SLE) in South Korea. Method: Two hundred and one patients with SLE were enrolled at the Rheumatology clinic of Seoul National University Hospital. Direct, indirect and total costs and HRQOL were measured using hospital electronic data and face-to-face interview. Socio-demographic and clinical factors associated with cost of illness and HRQOL were analyzed using multiple regression and multivariate logistic regression. Results: The average total cost of illness was estimated to be KRW 9.82 million (US 8993) per year, of which 41.6% was accounted for by direct costs and 58.4% by indirect costs. In multivariate regression, patients with renal involvement and those with depression incurred an average increment in annual total costs of 37.6% ( p = 0.050) and 49.1% ( p = 0.024), respectively, and an average increment in annual direct costs of 26.4% ( p = 0.050) and 43.3% ( p = 0.002), respectively, compared with patients without renal involvement and depression, respectively. In addition, disease damage was positively associated with an average increment in annual total and direct costs (55.3%, p = 0.006; 33.3%, p = 0.013, respectively), and the occurrence of indirect costs (OR 2.21, 1.09–4.88). There was no significant difference in HRQOL between patients with and without renal involvement (0.655 vs. 0.693, p = 0.203) Conclusion: Renal involvement, depression, and disease damage were major factors associated with higher total and medical costs for patients with SLE in South Korea. Effective treatment of renal disorders and depression may reduce the high economic burden of SLE.